The evolution of arsenic excess induced by thermal annealing in arsenic-rich Ga1-xAsx films - Campomanes, R. R.; Vilcarromero, J.; Galzerani, J. C.; Da Silva, JHD (Springer, 2005)
The evolution of As excess in As-rich Ga1-xAsx films is analyzed for distinct As concentrations and different annealing temperatures. Initially the samples are amorphous and crystallize partially after thermal annealing. The formation of both amorphous and crystalline As clusters is examined by micro-Raman and X-ray diffraction analysis. When highly and moderately unbalanced materials are compared, differences are clearly observed concerning the crystallization temperature and the migration kinetics of the As excess. These differences are explained by the fort-nation of As precipitates around the GaAs crystallites in the moderately unbalanced material, contrasting with the migration of the As excess to the film surface in the highly unbalanced material.